Pemberdayaan Ibu Melalui Bot Stoptunting Dalam Pemantauan Status Gizi Balita Untuk Penanggulangan Stunting Di Wilayah Kerja Posyandu Cempaka Pondok Meja - Marcella Faomasi Nazara, Irene; Asrie Dravika, Mutiara; Qalami Hadist, Najmi; Ridwan, M. (Jurnal Syntax Fusion, 2023)
Stunting is the most common form of child malnutrition with an estimated 161 million children worldwide in 2013 falling below 2 SD from the median child growth standard according to WHO. Muaro Jambi Regency reached 27.2% which is the highest figure for Jambi Province. Meanwhile, the stunting target in the RPJMN is to reduce the stunting rate to 14%. Seeing the problem of stunting in Muaro Jambi Regency, especially in Pondok Meja Village, the community service team considered the existing problems. The activities of the STOPTUNTING Bot team will be carried out in November-December 2022 at Posyandu Cempaka Pondok Meja. The method of implementing the activity uses FGD techniques, socialization of stunting and demonstrations of using the STOPTUNTING Bot. The results of this activity were from 9 mothers who had stunted toddlers in the Posyandu Cempaka Pondok Meja work area. 7 mothers who had stunted use and utilized the STOPTUNTING Bot to the maximum with a proportion of 77.7% during our activity.